Compare and propose improved method of risk assessment of damages due to lightning - Le , Quang Trung; Quyen, Huy Ánh; Phan, Chí Thạch (Journal of Technical Education Science, 2015)
This paper compares and analyzes method of risk assessment of damage caused by lightning between IEC 62305-2 standard and AS/ANZ 1768 standard; and proposes improved method of risk assessment of damage due to lightning base on the calculation method, recommended by IEC 62305-2 standard, with some additional and more detailed calculations proposed by AS/ANZ 1768 standard and shielding factor along the distribution line proposed by IEEE 1410 standard. The LIRISAS program calculates the risk of damage due to lightning is built on the improved method of risk assessment. This program haves the reliable result, high accuracy and the user utility.